Optimal Dispatch of a Virtual Storage Plant Using Inexact ADMM - Cai, Defu; Wang, Zuowei; Wang, Xiao; Wang, Yang; Wang, Wenna; Zhou, Kunpeng; Yu, Dehua (Frontiers in Energy Research, 2022)
Virtual Storage Plant (VSP) is identified as an effective approach aggregating distributed storage devices participating in power network supports with similar capability as bulk storage systems. In this paper, we develop a distributed control framework for cost-effective storage coordination in distribution networks, in which energy storage units contribute to a given power reference at the aggregated level, while regulate the local voltages in the presence of renewable generations. The salient feature of the proposed VSP control roots from the successful employment of an inexact alternating direction method of multiplier (ADMM) algorithm, in which the primal updates have analytical solutions in closed form using proximal operators, thus significantly reducing the computation efforts of individual storage agents. The proposed control is favorable for nearly real-time storage dispatch, and its effectiveness is demonstrated using realistic distributed networks in the simulations.